Faktor-Faktor Penentu Ketimpangan Pembagian Pendapatan di Provinsi Kepulauan Bangka Belitung - Desrifa Nurrahmah Cahyani; Duffan Anatoni; Marisa Adilah Putri; Rizky Setiawan (Journal of Economics Research and Policy Studies, 2026)
This study examines the persistent issue of income inequality in the Bangka Belitung Islands Province, where the mining sector largely drives economic activities. Despite steady economic growth, income distribution remains uneven across the population. This research aims to analyze the effects of education, economic growth, and population on income inequality during the 2019–2023 period. Using panel data regression analysis, the Fixed Effect Model (FEM) was identified as the most appropriate approach. The data were obtained from the Central Statistics Agency (BPS). The results indicate that, collectively, education, economic growth, and population have a significant impact on income inequality. However, partially, only education shows a statistically significant and negative effect. This suggests that higher levels of education help reduce inequality by improving skills and productivity. Therefore, expanding access to education and promoting labor-intensive industries are essential policy measures to achieve a more equitable income distribution in the region.